Impact of telephone follow-up and 24/7 hotline on 30-day readmission rates following aortic valve replacement -A randomized controlled trial. (1st February 2020) - Danielsen, Stein Ove; Moons, Philip; Sandvik, Leiv; Leegaard, Marit; Solheim, Svein; Tønnessen, Theis; Lie, Irene
Abstract: Background: Thirty-day all-cause readmissions are high after aortic valve replacement (AVR). We aimed to assess the effectiveness of a structured telephone follow-up (TFU) and a 24/7 hotline on reducing 30-day all-cause readmission (30-DACR) after AVR, on reducing symptoms of anxiety and depression and on improving perceived health state. Methods: A prospective randomized controlled trial was conducted. Patients (n = 288) were randomly allocated to either post-discharge usual care or to care that provided TFU and access to a 24/7 hotline after AVR. Ancillary endpoints were time-to-event (readmission), proportion of avoidable versus unavoidable readmissions after AVR, and predictors of 30-DACR after AVR. Results: 30-DACR was 22.3%. The structured TFU and 24/7 hotline intervention failed to reduce 30-DACR rates after AVR ( P = 0.274). Symptoms of anxiety were significantly reduced 30 days after surgery ( P = 0.031), an effect that did not persist one year after surgery ( P = 0.108). Most readmissions occurred before 15 days post-discharge, and 75% of them were deemed to be unavoidable. Pleural drainage before hospital discharge ( P = 0.027) and symptoms of anxiety before surgery ( P = 0.003) were predictors of 30-DACR after AVR. Conclusion: The TFU and 24/7 hotline had no effect on reducing 30-DACR after AVR. However, we did measure reduced symptoms of anxiety the first month after AVR. Anxiety reduction appeared to be an important target for intervention, because we found it to be a risk factor for readmission. Future research should focus on the effectiveness of interventions to prevent avoidable unplanned readmissions. Trial registration : ClinicalTrial.gov, NCT02522663 . Graphical abstract: Highlighted illustration: Kaplan-Meier curves illustrating the results of the time-to-event analysis on the thirty-day all-cause readmission rate between the groups in the AVRre study. Unlabelled Image